Pain in cancer and psychological methods of its personalized correction - Rybin, A. I.; Rybina, I. P. (Journal of Education, Health and Sport, 2020)
Physical pain can be a major component of cancer patient’s suffering but suffering itself covers much more different sides of a human being than physical manifestations and often happens in the absence of physical pain. Suffering or total pain include physical pain, social pain, psychological pain and spiritual pain, which have a mutual influence on each other. The efficacy of treatment of total pain in cancer patients may be increased by additional use of psychological methods of its correction.